2001
DOI: 10.1902/jop.2001.72.5.590
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cytokines and Inducible Nitric Oxide Synthase in Inflamed Gingival Tissue

Abstract: The expression of IL-6 may reflect inflammation in gingival tissue, and iNOS may be involved in the inflammatory process in periodontitis. The presence of A. actinomycetemcomitans or P. gingivalis might relate to the different cytokine profiles of IL-1alpha, IL-8, and IL-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
122
2
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(138 citation statements)
references
References 43 publications
6
122
2
8
Order By: Relevance
“…iNOS activity was reported to increase in ligatureinduced periodontitis [27], experimental periodontitis [30], and chronic periodontitis [20,26,31]. Higher levels of iNOS expression were observed in chronic periodontitis tissues than in clinically healthy gingival tissues [20,23,26,27,31] and a previous study of ours showed that iNOS increased in the gingival tissue of aggressive periodontitis patients (unpublished data). In various animal models iNOS was susceptible to infections by a variety of pathogens [32][33][34][35].…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…iNOS activity was reported to increase in ligatureinduced periodontitis [27], experimental periodontitis [30], and chronic periodontitis [20,26,31]. Higher levels of iNOS expression were observed in chronic periodontitis tissues than in clinically healthy gingival tissues [20,23,26,27,31] and a previous study of ours showed that iNOS increased in the gingival tissue of aggressive periodontitis patients (unpublished data). In various animal models iNOS was susceptible to infections by a variety of pathogens [32][33][34][35].…”
Section: Introductionsupporting
confidence: 57%
“…NO has been implicated in the pathogenesis of apical infection [45], periapical granulomas [46], and inflamed human dental pulp [47]. Increased iNOS expression in gingiva was shown in periodontitis [20,22,26,28,31], ligature-induced periodontitis [27], experimental periodontitis [30,46], inflamed gingiva [23], localized aggressive periodontitis [21], and recently by our group in aggressive periodontitis (unpublished data).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…6,21 IL-10 is expressed in both healthy and diseased human periodontal tissues and is reported to be reduced in patients infected with Aggregatibacter actinomycetemcomitans. 22 The gene encoding IL-10 was mapped to chromosome 1q31-32. The three SNPs(-1082 G/A; -819 C/T and -592 C/A) from the transcriptional start site have been associated with the altered synthesis of IL-10 in response to inflammatory stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The inducible isoform (iNOS) produces high quantities of NO when stimulated by many proinflammatory cytokines and is expressed in several types of inflammatory cells (Ricciardolo et al, 2004). The main neurotransmitters of excitatory NANC neurotransmitter are substance P (SP) and neurokinin A (NKA), which play significant roles in priming and recruiting of inflammatory cells and are also related to the pain and neurogenic inflammation presented in PD (Hirose et al, 2001).…”
Section: Introductionmentioning
confidence: 99%